2018
DOI: 10.1002/jcp.27303
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anticancer effects of cerium oxide nanoparticles on mouse fibrosarcoma cell line

Abstract: Cerium oxide nanoparticles are associated with anticancer effects. While protecting normal cells, these nanoparticles exert their anticancer effects via oxidative stress and apoptosis in the cancer cells. In this study, the anticancer properties of nanoceria on fibrosarcoma cell line are evaluated. Cerium oxide nanoparticles were synthesized by the coprecipitation method and their anticancer effects on mouse fibrosarcoma tumor cells (WEHI164) were investigated. Viability assay was evaluated by MTT, and the DC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(47 citation statements)
references
References 41 publications
(70 reference statements)
1
42
0
Order By: Relevance
“…Therefore NPs could accumulate in the blood and higher levels could be reached over time in the placenta [ 58 ]. We also used higher concentrations in this study that allowed us to make a complete cytotoxicity evaluation to determine the IC50 of CeO 2 NPs, which was not reached at 24 h of exposure and was 320 μg/mL (50.4 μg/cm 2 ) at 48 h. These high concentrations also allow further comparison of toxicity between placental and other barriers (especially pulmonary or intestinal) and may correspond to a worst-case scenario knowing that CeO 2 NPs are now being proposed as potential medicine (with actually-tested concentrations reaching up to 250 µg/mL) [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore NPs could accumulate in the blood and higher levels could be reached over time in the placenta [ 58 ]. We also used higher concentrations in this study that allowed us to make a complete cytotoxicity evaluation to determine the IC50 of CeO 2 NPs, which was not reached at 24 h of exposure and was 320 μg/mL (50.4 μg/cm 2 ) at 48 h. These high concentrations also allow further comparison of toxicity between placental and other barriers (especially pulmonary or intestinal) and may correspond to a worst-case scenario knowing that CeO 2 NPs are now being proposed as potential medicine (with actually-tested concentrations reaching up to 250 µg/mL) [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“… 30 Fibrosarcoma cell line (WEHI164) Conc. of nanoceria ≥ 15.63 µg/mL showed toxicity effects in cancer cells via increasing ROS levels and apoptosis [ 146 ] …”
Section: Biomedical Applications Of Nanoceriamentioning
confidence: 99%
“…(100 and 200 µg/mL) for 24 h. They observed that the cells incubated with CNPs showed much higher production of intracellular ROS and induced higher cytotoxicity because of increased cellular uptake as compared to CMPs. Recently, in 2018, Nourmohammadi et al [ 146 ] studied the anticancer activity of nanoceria against fibrosarcoma cell line (WEHI164), which showed dose-dependent cytotoxicity of nanoceria. They observed that nanoceria exposure with conc.…”
Section: Biomedical Applications Of Nanoceriamentioning
confidence: 99%
“…The pH-dependent redox activity of nanoceria is used for the selective induction of apoptosis in cancer cells [11][12][13][14]. In particular, it has been shown that nanoceria modulate intracellular signalling pathways, causing selective death of fibrosarcoma cancer cells [15]. Dextran-stabilised cerium oxide nanoparticles have been used to prevent tumour invasion in tumour-stroma interaction [16].…”
Section: Introductionmentioning
confidence: 99%